DECISION SUPPORT SYSTEM FOR SELECTING THE BEST TEACHER BASED ON PERFORMANCE APPRAISAL AT SMPIT AS SU'ADAA USING THE SIMPLE ADDITIVE WEIGHTING (SAW) METHOD - Ulfasari; Husin, Arif Ismail (Transpublika Publisher, 2022)
One of the efforts in improving the quality of human resources is to measure the performance of a teacher through a teacher selection. One of the information systems needed is a decision support system for selecting the best teacher. This is needed because the Principal and the Curriculum Section in the process of assessing teacher performance and determining the results of the best teacher selection decisions still use manual methods and do not have a decision support system and there is no appropriate method in selecting the best teachers. This research aims to create a decision support system with the Simple Additive Weighting (SAW) method, and create a MySQL database to store all data. The selection of the best teacher is determined by summing up the results of the assessment of existing criteria with predetermined weight. The results will be ranked according to the calculations in the Simple Additive Weighting (SAW) method. By applying the basic additive weighting method, design systems support principals and the curriculum department in identifying the most effective teachers based on measurable, objective performance indicators.